Hubungan antara pengetahuan dan perilaku ibu dalam pemberian ASI Eksklusif di Posyandu Tahun 2015 - Natya Ayu Pramudita; Heni Puji Wahyuningsih; Hesty Widyasih (Jurnal Kesehatan Ibu dan Anak, 2016)
Infant Mortality Rate in Indonesia is mostly caused by diarrhea and pneumonia.These diseases can be anticipated by givingexclusive breastfeeding to infants. Exclusive breastfeeding has a role in morbidity, mortality, growth and development, andIQ of babies. One of the factors that influence exclusive breastfeeding is knowledge. The percentage of exclusivebreastfeeding in the province in 2013 was66.7% and Bantul Regency is the one experiencing the declining percentage. Thelowest percentage was in the Public Health Center of Sewon I, that is 26.14%. Sewon I Health Center supervises 43Posyandus. Posyandus Menur and Mekarsari are the ones that have the most number of infants aged 6-24 months. Thisstudy aims to determine the relationship between knowledge and behavior of mothers in exclusive breastfeeding. This typeof research is analyticsurvey method with cross-sectional design. The research was held inApril 2015. The instrument usedis questionnaire. The research took place at Posyandu Menur and Mekarsari. These populations are mothers with babiesaged 6-24 months a number of 46 people and the sampling technique used is sampling saturated sampling technique whenail members of the population used as a sample. Results of this study there was no association between knowledge andbehavior with chi-square value of 2.469 (r>-0.116> 0.05). Midwives of Sewon I health center are expected to conduct anevaluation matteraffectingexclusivebreastfeeding beyond the knowledge and the cadres areexpected to provide support tomothers inorder to provide exclusivebreastfeeding.